Penerapan Program Tahfidzul Qur’an dan Implikasi Terhadap Akhlak Siswa di SMP IT Ar-Risalah Sukoharjo - Funky Marantika Nadia First; Nurul Latifatul Inayati; Mario Kasduri (UMSU, 2022)
This study aims to describe the application of the Qur’an tahfidz program and its implication for the morals of students at SMP IT Ar-Risalah Sukoharjo. Researchers used a qualitative approach with descriptive analysis. Researchers collected data by using interview, observation and documentation studies. The result of this study are that first, the application of program classically, tahfidz week, mabit, tahfidz quarantine, Qur’an camping. Second, the method used in memorizing the Qur’an. Third, obstacles in the implementation of the tahfidz program. Fourth, the supporting factors for the tahfidz program. Fifth, evaluation of the tahfidz program. Sixth, the implications of implementing the tahfidz program with students moral.